Spatial distribution of public green areas and their relationship with socioeconomic factors: a case study in the Jatiúca neighborhood, Maceió-Brazil - Lima, Bárbara Victória Pereira; Lopes, Franciany Prudente França; Barbosa, Ricardo Victor Rodrigues (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – To analyze the distribution of public green areas in the Jatiúca neighborhood, in Maceió-AL, considering its relationship with socioeconomic and urban factors, as well as green equity.Methodology – The study employed a literature review, geoprocessing techniques in QGIS software, and the overlay of socioeconomic data, applying the 300-meter buffer method to assess accessibility to green areas. Additionally, on-site visits were carried out at the Vera Arruda Corridor, with structured interviews conducted with users and thermal parameter measurements taken to evaluate comfort conditions.Originality/Relevance – The research is framed within the debate on green equity in tropical coastal cities, highlighting the deficit of green areas in the lower-income sectors of Jatiúca and the historical favoring of wealthier regions. It contributes to understanding how urban inequalities are reflected in the distribution of environmental assets.Results – The study found that higher-quality green areas are concentrated in wealthier sectors (New Jatiúca), while Old Jatiúca shows a deficit of vegetated spaces, lower accessibility, and more disorganized density. Measurements confirmed that tree-covered areas present better thermal comfort conditions. Interviews revealed demands for safety, lighting, accessibility, and more diverse facilities.Theoretical/Methodological Contributions – The research reinforces the importance of integrating geoprocessing, socioeconomic analysis, and thermal comfort assessment as an interdisciplinary approach to understand the effects of vegetation in the urban environment.Social and Environmental Contributions – The findings highlight the need for public policies that promote socio-environmental justice, prioritizing the expansion of vegetation and infrastructure in areas historically deprived of green spaces, in order to guarantee the right to the city in a more equitable and sustainable way.
Keywords: Urban planning; Urban green areas; Green equity; Sociospatial segregation